Holter ST monitoring early after acute myocardial infarction: mechanisms of ischaemia in patients treated by thrombolysis. Issue 5 (November 1993) - Stevenson, R N; Marchant, B G; Ranjadayalan, K; Uthayakumar, S; Timmis, A D
Abstract : OBJECTIVE–To investigate the mechanisms of Holter ST shift in patients with acute myocardial infarction treated by thrombolysis. DESIGN–Prospective observational study. SETTING–A London district general hospital. SUBJECTS–The study group consisted of 94 patients with acute myocardial infarction treated by thrombolysis. INTERVENTIONS–All underwent early 48 hour Holter ST monitoring and elective coronary arteriography. MAIN OUTCOME MEASURES–Relation of Holter ST shift to multivessel coronary disease, coronary patency, collateralisation, and morphology of the infarct related lesion. RESULTS–There was a trend towards an increased prevalence of Holter ST shift in patients with patency of the infarct related artery and those with multivessel disease. This was only significant in patients with three vessel disease, a significantly higher proportion of whom had > 3 episodes of ST shift (41% v 14%; p = 0.02) or a total duration of ST shift > 1 hour (35% v 13%; p = 0.04) than those with less extensive coronary disease. Holter ST shift occurred in a significantly higher proportion of patients with complex lesion morphology (Ambrose type 2 or 3) compared with those with lesions of Ambrose morphology type 1 or 2 (60% v 33%; p = 0.05). CONCLUSION–Holter ST shift detected early after thrombolysis is an ischaemic phenomenon with a complex pathophysiology. It reflects both remote ischaemia in patients with multivessel disease, and dynamic ischaemic processes related to complex lesion morphology in those with a patent infarct related artery.